Primary ovarian hydatid cysts: A case series of two cases (Indian Journal of Case Reports, 2022)
Hydatid disease is caused by the adult and the larval stage of tapeworms belonging to the Echinococcus species. The major sites of its infection are the liver and lungs. Rarely, it affects the pelvic region including the ovary, accounting for 0.2–2.25%. The primary ovarian site is a rare finding. We report here a case series of two cases with hydatid cysts as the left ovarian and tubo-ovarian masses. In case 1, a 30-year-old woman complained about lower abdominal pain with swelling and had a 7-month-old child and amenorrhea. Ultrasonographic report exhibited multiple cysts in the ovary. In case 2, a 23-year-old female was having primary left ovarian mass and clinically reported an ovarian dermoid tumor after ultrasound scan and had abdominal lump with pain. Her vital indices were normal. The biopsy was sent for further investigation.